Waviness at dry high-speed face milling of some hard steels - Irina Beşliu-Băncescu; Laurenţiu Slătineanu; Margareta Coteaţă (Metrology and Measurement Systems, 2021)
Waviness is a parameter used to complete information on the machined surface state. There is little scientific and technical information on the influence exerted by the cutting conditions and the workpiece material hardness on the values of some parameters that define the waviness of milled surface. No works have been identified to present such information for dry high-speed face milling applied to hard steel workpieces. A factorial experiment with four independent variables at three variation levels was planned to model the influence of milling speed, feed, cutting depth, and steel hardness on the total heights of the profile and surface waviness for dry high-speed face milling. Mathematical processing of experimental results was used to identify the power type function and empirical mathematical models. These models highlight the direction of variation and the intensity of influence exerted by the considered input factors on the values of two waviness parameters in the case of dry high-speed face milling of samples made of four hard steels. It has been observed that the increase in steel hardness increases the total heights of the profile and surface waviness. In the case of two types of steel, a good correlation was identified between the values of the total profile waviness height and the total surface waviness height, respectively, using the Pearson correlation coefficient.